UJI KELAYAKAN MODUL MINAT BELAJAR - Rachman, Indah Yuliana; Supriatna, Ecep; Septian, Muhammad Rezza (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2024)
In 2020, almost all countries have been affected by the COVID-19 outbreak, which requires students to study at home, this is considered ineffective and causes boredom. In the end resulted in a decrease in interest in learning in students. Interest in learning is one of the most important factors for the success of learning that students have. This article aims to determine the feasibility of teaching materials for the learning guidance and counseling service module in developing the learning interest of class VII students of SMP Negeri 1 Rengasdengklok. This study uses a quantitative approach with the Research and Development (RnD) method found by Bord and Gall to produce a product by going through one of the stages, namely the validation test. The validation test process involved 3 experts, two lecturers and one guidance and counseling teacher. Analysis of the data using a descriptive percentage of the results of the expert test of the product developed to get the feasibility with the media expert assessment of 96.80%, the material expert assessment of 92.64%, and the practitioner's assessment of 96.66%. The instrument used is a Likert scale validation questionnaire instrument. Then the product of the guidance and counseling service module for interest in learning meets the eligibility standards in the very feasible category for use. Thus, it can be concluded that the learning interest guidance and counseling module is suitable for use by class VII students.